The Palgrave Handbook of African Colonial and Postcolonial History (Palgrave Macmillan US, 2018)
This wide-ranging volume presents the most complete appraisal of modern African history to date. It assembles dozens of new and established scholars to tackle the questions and subjects that define the field, ranging from the economy, the two world wars, nationalism, decolonization, and postcolonial politics to religion, development, sexuality, and the African youth experience. Contributors are drawn from numerous fields in African studies, including art, music, literature, education, and anthropology. The themes they cover illustrate the depth of modern African history and the diversity and originality of lenses available for examining it. Older themes in the field have been treated to an engaging re-assessment, while new and emerging themes are situated as the book's core strength. The result is a comprehensive, vital picture of where the field of modern African history stands today.